2014
DOI: 10.1016/j.bbadis.2013.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin1 and autophagy protect cells from fluoride-induced cell stress

Abstract: Sirtuin1 (SIRT1) is an (NAD+)-dependent deacetylase functioning in the regulation of metabolism, cell survival and organismal lifespan. Active SIRT1 regulates autophagy during cell stress, including calorie restriction, endoplasmic reticulum stress and oxidative stress. Previously, we reported that fluoride induces endoplasmic reticulum (ER) stress in ameloblasts responsible for enamel formation, suggesting that ER-stress plays a role in dental fluorosis. However, the molecular mechanism of how cells respond t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
73
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 89 publications
6
73
0
Order By: Relevance
“…(46) Altogether, our results showed that the expression of three important groups of genes (EMPs, proteases, and SLCs) with major roles in amelogenesis was affected by exposure to both agents.…”
Section: Mmps)mentioning
confidence: 56%
“…(46) Altogether, our results showed that the expression of three important groups of genes (EMPs, proteases, and SLCs) with major roles in amelogenesis was affected by exposure to both agents.…”
Section: Mmps)mentioning
confidence: 56%
“…The results reported in a previous study [Suzuki and Bartlett, 2014] led us to believe that autophagy is involved in the regulation of dental fluorosis as well as protein synthesis and enamel mineralization. However, further research was needed to illuminate the definite relationship between autophagy and apoptosis during dental fluorosis.…”
Section: Discussionmentioning
confidence: 93%
“…Previous investigations have shown that fluoride induces autophagy in the LS8 ameloblast cell line and in MC3T3-E1 osteoblastic cells [Suzuki and Bartlett, 2014;Wei et al, 2014]. However, few studies have investigated whether fluoride induces autophagy in the rat ameloblast cell line HAT-7.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of ameloblast-derived LS8 cells with high doses of fluoride induces ER-stress and the expression of unfolded protein response transcription factors in a dose-dependent manner, as well as caspase-mediated apoptosis [24,25]. Remarkably, fluoride treatment increases SIRT1 expression and phosphorylation, resulting in an elevated deacetylase activity [25], as well as decreases extracellular secretion of the proteinases matrix metalloproteinase-20 and kallikrein-4 [24].…”
Section: Discussionmentioning
confidence: 99%